Poor postnatal weight growth is a late finding after sepsis in very preterm infants. Issue 3 (4th November 2020) - Flannery, Dustin D; Jensen, Erik A; Tomlinson, Lauren A; Yu, Yinxi; Ying, Gui-Shuang; Binenbaum, Gil
Abstract : Objective: To characterise the association between sepsis and postnatal weight growth when accounting for the degree of growth restriction present at birth. Design: Retrospective matched cohort study using data from the Postnatal Growth and Retinopathy of Prematurity study. Participants were born with birth weights of <1500 g or gestational ages of <32 weeks between 2006 and 2011 at 29 neonatal centres in the USA and Canada. Sepsis was defined as a culture-confirmed bacterial or fungal infection of the blood or cerebrospinal fluid before 36 weeks' postmenstrual age (PMA). Growth was assessed as the change in weight z-score between birth and 36 weeks' PMA. Results: Of 4785 eligible infants, 813 (17%) developed sepsis and 693 (85%) were matched 1:1 to controls. Sepsis was associated with a greater decline in weight z-score (mean difference −0.09, 95% CI −0.14 to −0.03). Postnatal weight growth failure (decline in weight z- score>1) was present in 237 (34%) infants with sepsis and 179 (26%) controls (adjusted OR 1.49, 95% CI 1.12 to 1.97). Longitudinal growth trajectories showed similar initial changes in weight z-scores between infants with and without sepsis. By 3 weeks after sepsis onset, there was a greater decline in weight z-scores relative to birth values in those with sepsis than without sepsis (delta z-score −0.89 vs −0.77; mean difference −0.12, 95% CI −0.18 to −0.05). This significant difference persisted until 36 weeks or discharge. Conclusion: Infants with sepsis had similar early weight growth trajectories as infants without sepsis but developed significant deficits in weight that were not apparent until several weeks after the onset of sepsis.